Diagnostic Accuracy of Fine Needle Aspiration Cytology, Triple Test and Tru-cut Biopsy in the Detection of Breast Lesion - Agarwal, Nirmal Kumar; Choudhury, Dhirendra Nath; Minocha, Akshit (Asian Pacific Journal of Cancer Care, 2023)
Background and Objective: The majority of breast disorders present as palpable masses. While most breast lesions are benign and do not progress to cancer, the accuracy of diagnosis can be improved through a combination of preoperative tests, including physical examination, mammography, fine-needle aspiration cytology (FNAC), and Tru-cut needle biopsy (TCNB) or core needle biopsy (CNB). FNAC has gained popularity as the primary diagnostic procedure for solid and cystic breast masses following a history and clinical examination. This study aimed to evaluate the diagnostic accuracy of FNAC in comparison to the Triple Test and TCNB for breast mass diagnosis. Materials and Methods: The study was conducted at Tezpur Medical College and Hospital from January 2023 to May 2023. Female patients over the age of 20 with clinically palpable lumps were included. Complete clinical breast examination, imaging, and tissue sampling were performed to establish a definitive diagnosis and rule out cancer. Ultrasonography/Mammography, FNAC, and Tru-cut biopsy were performed concurrently in the same region, and the results were compared to the final histopathology as the gold standard. Results: The majority of patients in the study were in the age group >60 years. Among the patients, 41 (58.5%) had involvement in the left breast, while 29 (41.4%) had involvement in the right breast. The most common site involved was the upper outer quadrant in 38 (54.2%) cases. The overall sensitivity of FNAC in our study was 93.75%, while Tru-cut biopsy and the Triple Test showed a sensitivity of 100%. The specificity for malignancy was 91.6% for FNAC, 93.6% for Tru-cut biopsy, and 95.6% for the Triple Test. Conclusion: Each of the three techniques has its advantages and disadvantages. Core Needle Biopsy cannot replace FNAC and is not necessary for all breast lesions. It can be used as an adjunct in cases where cytology is definitive and biomarker testing is required. In our study, the Triple Test and Tru-cut biopsy demonstrated higher accuracy compared to FNAC. Tru-cut biopsy provided a histological diagnosis that was 100% consistent with the final histopathology report.